Data Warehousing Fundamentals A Comprehensive Guide for IT Professionals - Ponniah, Paulraj (New Delhi Wiley India, 2008)
This book provides an interactive learning experience, you will be able to study every significant topic in planning, requirements, architecture, infrastructure, design, data preparation, information delivery, deployment, and maintenance
Includes bibliographical references and index
11
Keywords: Data Warehousing -- Information; Data Warehousing